ANALYSIS OF INDUSTRIES BECOMING SICK BY RATIO ANALYSIS (Journal of Mechanical Engineering, 2014)
Industries becoming sick has become a great problem everywhere in this industrial world especially in the 3rd world countries. Many researches have been done to analyze the problem and suggest opinions about solving this problem as huge amount of capital is lost if an industry becomes sick and go out of business. If the numbers become multiple, such happenings might affect national economy and thus it draws attention of political and business leaders besides new entrepreneurs of the country. In this paper an attempt has been made to analyze this problem by using financial ratio analysis. Various financial ratios of two numbers of medium and large industries of one industrial corporation in Bangladesh have been calculated by using actual financial data of the industries. The data has been analyzed and a correlation has been shown with various financial ratios with the industries becoming sick. The authors hope that the findings of the analysis will attract attention of academicians, industrialists, political leaders, and the owners of the industries which are becoming sick and will also show a guiding path to new entrepreneurs. DOI: http://dx.doi.org/10.3329/jme.v44i1.19495